Discourse - Mills, Sara (Routledge, 2004)
This volume provides a broad analysis of the term 'discourse' and a thorough examination of the many theoretical assumptions surrounding it. In the revised edition of this invaluable guidebook, Sara Mills: *examines the historical definitions and developments of discourse *analyzes Foucault's use of the term and its appropriation in the fields of linguistics, social psychology, and feminist, colonial and post-colonial theory *explores the changes that have taken place in the field of critical discourse analysis since original publication *discusses the work of various discourse theorists, including Zizek and Bourdieu. A fully updated bibliography, new glossary and suggestions for further reading make this more than ever the essential introductory guide to the concept of discourse for students of literary theory.